Parental perceptions and experiences of kangaroo care for preterm infants in neonatal intensive care units in China: a qualitative study - Qian Cai; Yunxian Zhou; Danqi Chen; Fang Wang; Xinfen Xu (BMC, 2024)
Abstract Background kangaroo care (KC), endorsed by the World Health Organization, is an evidence-based intervention that plays a pivotal role in mitigating preterm infant mortality and morbidity. However, this intervention has not been fully integrated into healthcare systems in China. This study aimed to gain insight into parents' perceptions and experiences of KC for preterm infants to contribute to the KC implementation on a larger scale. Methods This study employed a descriptive qualitative design, using face-to-face, semi-structured, in-depth interviews. Fifteen parents participating in KC for preterm infants in the neonatal intensive care units (NICUs) were purposively sampled from four hospitals across four cities in Zhejiang Province, China. Thematic analysis was employed to analyze the data. Results Four themes and twelve subthemes regarding the parents' perceptions and experiences about KC were identified. The four themes included: (1) Low motivation upon initial engagement with KC, (2) Dynamic fluctuations of emotional states during KC, (3) Unexpected gains, and (4) Barriers to participation. Conclusions Parents' perceptions and experiences of KC was a staged process, with parents exhibiting distinct cognitive patterns and unique experiences at each stage. Overall, as KC progresses, parents' experiences tended to become increasingly positive, despite potential obstacles encountered along the way. To enhance the implementation of KC, healthcare providers could utilize prenatal and postnatal education programs. These programs aim to enhance the understanding of KC among parents of preterm infants, fostering sustained engagement in KC practices.